Frequency of Different Type of Anemias in Hypothyroid Patients: Cross-Sectional Study - Rafia Wajid, Qurrat-Ul-Ain, Sidra Kadir, Anum Sharif, Neelam Mazhar, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Thyroid hormones are essential for the normal mental and physical development but unfortunately, thyroid dysfunctions are common endocrine disorders. Aim: To determine the frequency and different type of anemia in hypothyroid patients. Study Design: Cross sectional study. Methodology: A total of 108 patients with hypothyroidism, 25 to 65 years of age were included. Pregnant women, history of blood transfusion within last one month, CLD & CRF were excluded. After this, 5ml blood sample was taken and sent to the institutional pathology laboratory for measuring hemoglobin and serum ferritin and presence or absence of anemia and its types was noted. The collected data was analyzed by using SPSS. Chi square ware applied with P-value< 0.05 as significant. Results: Age range in this study was from 25 to 65 years with mean age of 42.18 ± 8.64 years. In this study, frequency of anemia was found in 43 (39.81%) hypothyroid patients with 65.12% patients have normo-cytic normo-chromic anemia. Conclusion: It was concluded that frequency of anemia in hypothyroid patients was very high with normocytic normochromic anemia as the most common type.